Case reportCustom-designed mouthpiece for HDR brachytherapy of embryonal rhabdomyosarcoma of the soft palate - Ekwelundu, Emmanuel; Krasin, Matthew J.; Farr, Jonathan B. (Journal of Contemporary Brachytherapy, 2014)
This paper describes the design and fabrication of the mouthpiece used for high-dose-rate (HDR) brachytherapy of a cancerous lesion in the soft palate of a pediatric patient. A custom mouth guard made with Thermo-forming material (Clear – Mouthguard) similar to those used by athletes, with a bite section, alveolar sulcus, hard and soft palate sections was made. Markers were placed around the lesion using a color transfer applicator and the impression transferred to the mouthpiece. Ten catheters arranged in a plane were placed on the inferior side (concave part) of the mouthpiece, and held in place by stitching each to the mouthpiece. Two pieces of lead (Pb) sheets with total thickness of 5.7 mm were placed beneath the catheters. Wax was used to create additional distance between the tongue and the catheters, and the entire assembly was covered with wax.